Screening of a Small Spherical Macroion by Oppositely Charged Flexible Polyelectrolyte - Quyen, Vu Van; Yen, Vu Thi Hai; Toan, Nguyen The (Communications in Physics, 2017)
Electrostatic interactions play important roles in the assembly, the structureand the functions of many biological as well as soft matter systems. In the presence of a macro-ion in aqueous solution, oppositely charged molecules mobilize around it to screen out its electrostatic potential. In this paper, we focus on screening of small macroion by a flexible polyelectrolyteusing Monte-Carlo simulation. It is shown that the condensation of the polyelectrolyte around the macroion shows a first order phase transition from a dense to a dilute concentration of monomers. The width of the condensed region increases with stronger screening or with smaller macro-ion charges. For small macro-ion charge, or when the Coulomb interactions are strongly screened, no complexation between the polyelectrolyte and the macro-ion happens.Additionally, long polyelectrolyte protrudes both tails and loops from the macroion. This is quite different from the case of large macroions where only tails appear. Our results can be used to explain various experimental trends.